PERANAN PEMERINTAH DESA DALAM MENINGKATKAN PARTISIPASI MASYARAKAT DI BIDANG PEMBANGUNAN EKONOMI DI DESA RANCAPANGGUNG KECAMATAN CILILIN KABUPATEN BANDUNG BARAT - Paisal Nopiansyah; Agustina Setiawan; Dadan Kurnia (Jurnal Caraka Prabu, 2019)
This research entitled "The role of Village Government in Increasing Public Participation in Economic Development Village Rancapanggung Cililin District West Bandung Regency". The problem in this research is not optimal the Village Head in monitoring the development of society so that it can cause the lack of society in participating in planning, execution, utilization and also supervision and evaluation of economic development in Rancapanggung Village. As well as, concerning the low level of public awareness and lack of socialization of agencies that will carry out development activities to the community resulting in lack of ownership of the results of development and lack of coordination between agencies. The purpose of this study is to describe and analyze the Role of Village Government in Increasing Public Participation in Village Economic Development. The research method used is descriptive qualitative. Data collection techniques conducted by researchers is to learn to study books as reference materials, field observations, and interviews. In sampling the researcher using technique Purposive Sampling. Informants in this research are Village Head, Village Community Empowerment Institution, and Community Leader. From the research results found that the role of village government in improving community participation in the field of village economic development is still not optimal. There are several weak points such as (1) lack of village heads in monitoring the development of the community, (2) lack of community in participating in planning, implementation, utilization and monitoring and evaluation of economic development in Rancapanggung Village, (3) lack of socialization from agencies that will carry out development activities to the community, (4) lack of ownership of the development result and lack of coordination between agencies. Keywords: Role of Village Government, Community Participation, Development, Village Economy